Perceived academic achievement and school commitment in the context of school sports: A qualitative study based on students’, teachers’, and parents’ perspectives - Zeki Taş; Songül Baykara; Yılmaz Ünlü; Ayşe Önal; Ahmet Naci Dilek; Murat Şen (PLoS ONE, 2026)
School sports are widely associated with students’ academic and psychosocial development, yet their educational value cannot be fully understood through outcomes alone. How sports participation shapes academic achievement and school commitment depends on how it is experienced and interpreted by students, teachers, and parents. Examining these stakeholder perspectives is essential for understanding the perceived academic implications of school sports and their role within everyday school contexts. This study adopted a qualitative descriptive research design to explore perceptions of school sports and their perceived influence on academic achievement and school commitment. The study group consisted of 18 participants, including 6 high school students (grades 10–12), 6 parents whose children participated in school sports, and 6 physical education teachers working at a public high school in Sakarya, Türkiye. Participants were selected using criterion sampling. Data were collected through face-to-face focus group interviews conducted separately with each stakeholder group. The data were analyzed using descriptive qualitative analysis supported by inductive content analysis to identify recurring patterns and themes related to participants’ views and experiences of school sports. The findings indicate that school sports are perceived to positively influence students’ academic achievement and school commitment, particularly through increased motivation, concentration, and engagement with school life. Participants emphasized that sports participation strengthens emotional and behavioral commitment by enhancing feelings of belonging and active involvement in school activities. Teachers’ guidance and parents’ supportive attitudes were identified as key contextual factors, while students’ personal interest in sports shaped whether participation was experienced as supportive or demanding. This study concludes that school sports play a meaningful role in supporting students’ perceived academic achievement and school commitment when embedded within supportive school and family contexts. The findings highlight that the educational value of sports is shaped not only by participation itself but also by students’ experiences, teachers’ guidance, and parental support. By integrating multiple stakeholder perspectives, the study underscores the importance of aligning school sports practices with academic goals to foster sustained engagement and positive educational experiences.